The best worst day ever - Batterson, Mark; Dailey, Summer Batterson; Capriotti, Benedetta ([Colorado Springs, Colorado] : Multnomah, 2023)
"This whimsical rhyming picture book encourages young children to make the most of each day God gives"--Provided by publisher.
Keywords: Children's stories